2015
DOI: 10.1002/mus.24461
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a compartment syndrome–like injury model

Abstract: INTRODUCTION Acute compartment syndrome (CS) is caused by an elevation of pressure within a muscular compartment which can be caused by numerous factors, including blunt trauma. In this study, we characterized a rodent model of CS-like injury. METHODS Forty male athymic rats received a standardized injury of ischemia and compression to their hindlimbs, while the intracompartmental pressure (ICP) was measured using an implantable transmitter. Tetanic muscle function was evaluated, and histology was performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 39 publications
1
18
0
Order By: Relevance
“…Tissue edema and disorganization were early observed 24 h after injury, and within the first 4 days, 50% of the muscle fibres underwent degeneration. Immune cell infiltration, as described in other models, occurred within 2 days after damage and persisted throughout the first week, with a peak at day four [154][155][156]. Following the acute inflammatory response, fibroblast and myofibroblast growth resulted in enhanced collagen deposition, also supporting the formation of newly regenerating fibers.…”
Section: Crush Injury and Ischemia-reperfusion Damagesupporting
confidence: 54%
See 1 more Smart Citation
“…Tissue edema and disorganization were early observed 24 h after injury, and within the first 4 days, 50% of the muscle fibres underwent degeneration. Immune cell infiltration, as described in other models, occurred within 2 days after damage and persisted throughout the first week, with a peak at day four [154][155][156]. Following the acute inflammatory response, fibroblast and myofibroblast growth resulted in enhanced collagen deposition, also supporting the formation of newly regenerating fibers.…”
Section: Crush Injury and Ischemia-reperfusion Damagesupporting
confidence: 54%
“…Indeed, although early markers of satellite cell activation such as Pax7 and MyoD were observed early after damage (2 days), regenerating myofibers were detected 7 days after injury in correspondence with the phase of collagen deposition (Figure 1) [154]. The extensive damage induced by muscle compression was also highlighted by signs of denervation, such as the dispersed localization of acetylcholine receptors around crushed myofibers and of vasculature alterations, including neo-angiogenesis preceded by the presence of enlarged vessels and hemorrhagic areas [154,156,157].…”
Section: Crush Injury and Ischemia-reperfusion Damagementioning
confidence: 98%
“…Experimental evidence suggests that in ammation is one of the main driving factors of secondary injury following ACS [32][33][34]. Recent studies have shown that transplanted MSCs reduce IRI in skeletal muscle by inhibiting the in ammatory response and oxidative stress [35,36] while promoting muscle tissue repair after injury [37].…”
Section: Discussionmentioning
confidence: 99%
“…Fortunately a rare occurrence, a phlebotomy tourniquet left in place for prolonged periods of time (e.g., hours) can result in the development of extremity compartment syndrome-a potentially limb-threatening condition [106,107]. Compartment syndrome is a serious injury defined by an increase in pressure within a fascia-enclosed muscle compartment that results in compromised circulation leading to nerve damage and muscle necrosis [108]. This can lead to permanent disability, amputation, or even death from the release of toxic metabolites.…”
Section: Special Topicsmentioning
confidence: 99%